2005
DOI: 10.1352/0895-8017(2005)110[439:laospa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Stereotypic, Proto‐Injurious, and Self-Injurious Behavior Exhibited by Young Children With Developmental Delays

Abstract: Twelve children (CA, 12 to 32 months) with developmental delay were observed in their homes during monthly analogue functional analysis probes to document patterns of emerging self-injurious behavior. Two patterns of emerging self-injury were observed for 5 participants: (a) The topography and functional analysis pattern remained the same, but the behavior eventually caused tissue damage; or (b) a new topography emerged that was similar to an established stereotypic motor behavior. Functional analysis results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
99
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 28 publications
9
99
1
1
Order By: Relevance
“…In a study of an institutional population with intellectual disabilities, the most common forms of self-injurious behavior that were observed in more than 10% of the cases were self-slapping, self-scratching, head banging, selfbiting, and self-smearing (Saloviita, 2000). Similar results have been reported in other studies (Richman & Lindauer, 2005;Taylor, Oliver, & Murphy, 2011).…”
Section: Introductionsupporting
confidence: 82%
“…In a study of an institutional population with intellectual disabilities, the most common forms of self-injurious behavior that were observed in more than 10% of the cases were self-slapping, self-scratching, head banging, selfbiting, and self-smearing (Saloviita, 2000). Similar results have been reported in other studies (Richman & Lindauer, 2005;Taylor, Oliver, & Murphy, 2011).…”
Section: Introductionsupporting
confidence: 82%
“…This finding is difficult to interpret in terms of the current literature on proto-injurious behavior, given that there does not appear to be any topographical association between stereotyped behaviors that predicted SIB, especially with regard to yelling. That is, previous research (Guess & Carr, 1991;Richman & Lindauer, 2005) has suggested that some forms of SIB may evolve from topographically similar forms of stereotyped behavior such as hand flapping in the head and shoulder region evolving into head hitting.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that some proto-SIBs seemed to lead to SIBs of similar topographies. Richman and Lindauer (2005) followed emerging patterns of SIB in very young children with moderate-to-profound developmental delays. They confirmed that the majority of the proto-SIB remained topographically unchanged as they morphed into SIB for some of the children that developed SIB during the course of the study.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…These reactions may inadvertently reinforce SIB through operant learning processes, increasing its future probability and establishing a maladaptive behavioral repertoire that persists. Ultimately, SIB is the product of interactions stemming from deficits secondary to the developmental disability and experiences that occasion and reinforce SIB through operant learning processes [6,29,30]. Although the processes that lead to the emergence of SIB are not fully known in general, nor can they be identified in any a given case, the variables that currently maintain SIB through reinforcement can be identified through functional behavioral assessment in the majority of cases.…”
Section: Functional Behavioral Assessment and Classificationmentioning
confidence: 99%